Kaposi Sarcoma After Kidney Transplantation (Iranian Journal of Kidney Diseases, 2009)
Skin cancers are the most common tumors among transplant recipients who receive immunosuppressive agents. Kaposi sarcoma (KS) is one of the most common malignancies to occur in kidney transplant recipients, especially in the Middle East countries. Its prevalence in comparison with other neoplasms is also relatively higher in Iran (> 35%). The KS-associated herpesvirus or human herpesvirus 8 is a newly discovered herpesvirus found in all forms of the KS including those among immunosuppressed transplant recipients. Kaposi sarcoma usually regresses after withdrawal or reduction of immunosuppressive agents. A wide variety of therapies have been used for KS, including radiotherapy and administration of interferon and different chemotherapeutic regimens. Sirolimus exhibits antiangiogenic activity related to impaired production of vascular endothelial growth factor and limited proliferative response of endothelial cells to the stimulation by vascular endothelial growth factor. Therefore, it can inhibit the progression of KS. Accordingly, replacement of calcineurin inhibitors by a sirolimus can show promising results in the prevention of KS.